Physics and applications: Quantum optics - Messikh, Az Eddine; Youssouf , Hamidou Issoufa (Uniwesytet zielonogorski, 2012)
Quantum optics was born in the first years of the 20th century. The first papers leading to further ideas of quanta of light were presented by Max Planck and Albert Einstein. Their pioneering papers laid the foundations for the theory of quantum optics. However, one should remember that for the birth of the formal theory of quantisation of light, the development of quantum mechanics was necessary. Interestingly, the word ’photon’ appeared for the first time in a paper by a Gilbert Lewis, a chemist, in 1926 and was later used by P.A.M. Dirac, a physicist, the next year. The modern sense of the term quantum optics was established in 1956 when Hanbury Brown and Twiss built the intensity interferometr and performed their famous experiment in which correlations between two light beams were measured. Although the results of their experiment could be explained on the basis of the classical theory of light, with some quantumcomponent to the process of photodetection, their result is commonly accepted as the beginning of the modern quantum optics era. The next milestone in the development of quantum optics was the invention of laser in 1960. The physical properties of the light generated by lasers were considerably different from those characterising the light generated by classical thermal sources. This fact was a great impulse leading to further development of quantum optics’ ideas. The first of them were presented in the fundamental papers written by Glauber, describing new states of light quantum coherent states.